Performance Analysis of The Triple Elimination Checking Programme for Pregnant Mothers in Antenatal Care at The Dinas Health District of Rokan Hilir Year 2024 - Riauni Syaputri; Budi Hartono; Emy Leonita; Novita Rany; Doni Jepisah (LPPM Universitas Harapan Bangsa, 2024)
The Triple Elimination Program aims to prevent the transmission of HIV, syphilis, and hepatitis B from mother to child. In Rokan Hilir Regency, screening coverage remains low: hepatitis B (42.2%), HIV (38%), and syphilis (48.3%). Bantaian Health Center has the lowest coverage, while Bagan Batu Health Center has the highest. A thorough evaluation is needed to improve program performance using the Malcolm Baldrige approach. This study aims to evaluate the performance of the triple elimination program for pregnant women at the Rokan Hilir District Health Office in 2024, employing a mixed-method explanatory sequential design. The sample consisted of 40 respondents and 9 stakeholders as informants. Triangulation was applied to sources, methods, and data. The results show that most respondents rated program leadership as high (57.5%), while strategic planning (52.5%), patient focus (62.5%), measurement and knowledge management (60%), team focus (55%), process focus (57.5%), and performance results (60%) were rated low. Qualitatively, program leadership demonstrated strong commitment. Program planning is based on technical guidelines and BOK funds, with limitations in APBD budget allocations. Education and collaboration with community leaders have been implemented. However, the program has not focused on patients and is not widely recognized by the community. Staff at Bantaian and Bagan Batu Health Centers enthusiastically implement the program despite limited human resources, introducing innovations and conducting regular evaluations. The program is developed through coordination meetings, data analysis, and cadre training. Key factors for achieving targets include case monitoring, health education, cross-sector collaboration, and periodic evaluations. Health centers need to expand education and socialization on the importance of triple elimination screening, supported by integrated coordination between the Health Office and related agencies (OPD).